The Role of the Gut Microbiota and Microbial Metabolites in the Pathogenesis of Alzheimer’s Disease - Wang, Yi (CNS & Neurological Disorders - Drug Targets, 2023)
Alzheimer’s disease is a neurodegenerative disease that causes memory loss, cognitive dysfunction and dementia. It is a multifactorial disease involving a wide range of pathological factors that have yet to be fully understood. As proposed by scientists and supported by a growing amount of evidence in recent years, the gut microbiota plays an important role in the pathogenesis of Alzheimer’s disease via a constant bidirectional communication through the brain-gut-microbiota axis, which is a multifunctional network involving the nervous system and the peripheral circulatory system. This communication pathway facilitates the exchange of information and signals between the brain and the gut, such as microbe-derived metabolites and neurotransmitters, which allows gut microbes to influence the central nervous system. This review summarizes recent research findings on the pathological risk factors of Alzheimer’s disease, the brain-gut-microbiota axis, the role of gut microbe-derived products in neurological disorders, and clinical/preclinical studies investigating the role of the gut microbiota in Alzheimer’s disease. In addition, some suggestions for future research are proposed.
Keywords: gut microbiota